2008
DOI: 10.1002/bit.21801
|View full text |Cite
|
Sign up to set email alerts
|

A role for microwave processing in the dry preservation of mammalian cells

Abstract: Dry preservation involves removing water from samples so that degradative biochemical processes are slowed and extended storage is possible. Recently this approach has been explored as a method for preserving living mammalian cells. The current work explores the use of microwave processing to enhance evaporation rates and to improve drying uniformity, thereby overcoming some of the challenges in this field. Mouse macrophage cells (J774) were pre-incubated in full complement media containing 50 mM trehalose, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…2 Recent studies indicated that the slow rate of drying in conventional techniques may be a reason for the failure, 5,41,48 and to develop a successful processing technique for lyopreservation, it is important to minimize the exposure time of the cells to the deleterious effects of supersaturated solutions. 5,28 For this reason, researchers have looked at developing several fast desiccation techniques for dry processing of cells including vacuum drying, 9 microwave drying, 16 and nebulization. 48 However, these fast drying techniques, depending on their drying mechanism, frequently expose cells to additional injury during processing.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent studies indicated that the slow rate of drying in conventional techniques may be a reason for the failure, 5,41,48 and to develop a successful processing technique for lyopreservation, it is important to minimize the exposure time of the cells to the deleterious effects of supersaturated solutions. 5,28 For this reason, researchers have looked at developing several fast desiccation techniques for dry processing of cells including vacuum drying, 9 microwave drying, 16 and nebulization. 48 However, these fast drying techniques, depending on their drying mechanism, frequently expose cells to additional injury during processing.…”
Section: Discussionmentioning
confidence: 99%
“…13 This approach yielded a more uniform dried product, and the drying rates achieved were very reproducible. However, processing was limited to a single sample at a time and the drying approach required manual stop and start operation to control temperature.…”
Section: Discussionmentioning
confidence: 92%
“…While this thermal titration effect could theoretically also be achieved by contact heating of the sample, microwave energy input has been shown to effectively interrupt gradient-driven mass transfer processes that lead to sample inhomogeneity, likely due to the volumetric nature of this energy delivery. 13 It is not clear whether or not contact heating would yield this same beneficial overall effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations